Sumber Pakan yang Berbeda terhadap Kecerahan Ikan Mas Koki (Carrasius auratus) - Mukti, Retno Cahya; Artika, Anjani Dini; br Napitupulu, Ernawati; Saputra, Muhammad Iqbal; Anila, Yunita; Maslamia, Ayu; Juniarti, Hanifa; Dianda, Andra (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Mukti RC, Artika AD, Napitupulu EB, Saputra MI, Anila Y, Maslamia A, Juniarti H, Dianda A. 2022. Different feed sources on the brightness of golfish (Carrasius auratus). In : Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 809-815. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Goldfish often find problems in ornamental fish cultivation, namely in terms of color and morphology of ornamental fish produced in Indonesia which are very unattractive, bright and bright fish colors are one of the main attractions of ornamental fish in determining their selling value, to determine the growth rate, increase in color brightness and carotenoid content of goldfish (Carrasius auratus) after being given additional feed in the form of indigofera flour, carrot flour and water hyacinth flour. The method used is a literature study by comparing the three types of feed, namely indigofera flour, carrot flour and water hyacinth flour. The results showed that several sources of -carotene in the feed gave different results in increasing the color brightness of goldfish. The 5% dose of indigofera flour and carrot flour was the best dose for the color brightness of goldfish, while the additional dose of water hyacinth flour given was the 300 g dose that was the best dose to support the color quality of goldfish (Carassius auratus). So, with the results of the three types there is a significant difference in the brightness level of goldfish color.